The COVID-19 Challenges to the Unfold of Entrepreneurship Education - Pelegrin, Mark Anthony; Rola, Marjorie; Nayve Jr., Ruben M. (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2023)
This article reviews and discusses along the development and deployment of universities’ entrepreneurship teaching and learning. It emphasizes on the detection, interpretation and analysis of entrepreneurial skill sets that can be directly established by structured educational programs. This analytical review and opinions also aims to illustrate and also describe how entrepreneurial discipline needs to evolve on the basis of the technological advancements that the current COVID-19 disaster has rendered reasonable to expect. The numerous relevant theories in entrepreneurial learning are indeed discussed, indicating the need to consider regarding future potential educational strategies in various possibilities. Some issues were established in a study of the previous research including the teaching substance, the teaching methodologies, the institutional characteristics and the proper teaching instructor that should deliver entrepreneurship education. The article concludes that educators should continuously evolve the instructional framework, practices, as well and instruction in response to an evolving entrepreneurship climate.